Iron NRT- and arc-displacement cross sections and their covariances. (May 2018) - Simakov, S.P.; Fischer, U.; Koning, A.J.; Konobeyev, A.Yu.; Rochman, D.A.
Highlights: The NRT - and arc -displacement cross sections for Fe were computed up to 200 MeV. The latest Neutron Reaction and Molecular Dynamics data were used. First time the total covariances were constructed. The calculated arc -damage agrees with measurements performed at fission reactors. Abstract: Displacement damage cross sections have been calculated for natural iron and its constituent individual isotopes based on the latest versions of the evaluated neutron data libraries ENDF/B-VIII.0 and TENDL-2017 using the conventional NRT and recently introduced athermal recombination-corrected ( arc) displacement concepts. Their covariance matrices, which quantify the uncertainties and the associated energy-energy correlations, were assessed for the first time based on TENDL-2017 random data files representing the covariances of the underlying nuclear data. In addition to the nuclear data, the covariances due to the ion energy partition, the primary defect survival efficiency and the lattice threshold energy were also propagated to the damage quantities. The arc -dpa was computed employing all available results from molecular dynamics and binary collision simulations. The comparison of the spectrum-averaged arc -dpa with the few available measurements at fission reactors has demonstrated a reasonable agreement within the experimental and calculation uncertainties. The comparison with the current NRT -dpa standard, provided by ASTM up to 20 MeV but without uncertainty, has indicated differences up to 8% above 0.5 keV and 60% below.